Bahasa Indonesia: Bahasa Inggris - Suraya Hidayati; Arsyad, Rini Nisponi (Institut Agama Islam Darul Ulum Kandangan, 2021)
The outbreak due to the Covid-19 pandemic that has hit the world, including Indonesia, provides opportunities for the economic development of halal product. People are increasingly concerned about product halal, including hygiene and benefits. This has a good impact on the growth and depelopment of world halal products in the future. The purpose of writing this article is as a reference material for local entrepreneurs to take advantage of the potential of the halal product industry, in addition to filling huge domestic needs as well as taking a role in the global trade in halal products. This study uses a descriptive qualitative method approach, using content analysis techniques and library research. The results show that halal products have spread to various sectors of demand, such as food products, halal tourism, clothing (fashion), media and recreation, pharmaceutical-cosmetics, and finance. Indonesia, with the largest Muslim community and the increasing needs of the world community for halal products, provides an opportunity for the Indonesian state to become one of the countries producing halal products, not only for its own needs, but also to meet the needs of the world halal market.